Pengaruh Model Contecxtual Teaching And Learning (CTL) Berbantuan Media Bingo Terhadap Hasil Belajar Peserta Didik Kelas III SD Negeri Latihan 2 SPG Ambon - Rahareng, Ana Patresia; Abdurrachman, Ode; Mahananingtyas, Elsinora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by bingo media on the learning outcomes of third-grade students at SD Negeri Latihan 2 SPG Ambon in the IPAS subject. The background of this research is the low student learning outcomes caused by conventional teaching methods that do not actively involve students. The research method used is quantitative with a One-Group Pretest-Posttest design. The research sample consisted of 36 third-grade students. Data collection instruments included tests, observations, and interviews. The statistical test results showed an increase in the average score from a pretest score of 66.17 to a posttest score of 89.97. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect of the CTL model assisted by bingo media on students' learning outcomes. The N-Gain score of 0.7539 indicates a high level of learning improvement. Based on these findings, the CTL learning model using bingo media is proven to be effective in improving students' learning outcomes in IPAS learning